Reactive power compensation of fixed speed wind turbines using a hybrid wind turbine technology - Apata, Oluwagbenga (Department of Electrical Engineering, 2022)
There has been significant growth in the use of wind energy as an alternative form of energy by many countries globally. This is in direct response to calls to reduce environmental pollution from the usage of fossil fuels in energy generation. Due to the intermittency of wind energy, the integration of wind energy into an existing power system grid can lead to increased exposure to instability. This has prompted power systems operators to revise the connection requirements for grid codes that require wind turbine generators to contribute to power control and stay online during a network disturbance. These revisions have resulted in technical migrations from the fixed speed wind turbine (FSWT) to the variable speed wind turbines (VSWTs). The fixed speed induction generator (FSIG) powers the FSWT while the VSWT is based on the permanent magnet synchronous generator (PMSG) or the doubly-fed induction generator (DFIG). Irrespective of this technical migration in wind power systems, the FSWTs still represent a considerable percentage of globally installed wind turbines (WTs). Furthermore, some wind turbine (WT) manufacturers have introduced life expansion programs for these FSWTs to increase their operating life to as much as thirty years. The FSWT is common in wind power systems due to its robustness, mechanical simplicity, and low production cost. Its major setback is the inability to compensate for its reactive power need and improve voltage stability during a fault condition. In steady-state conditions, these WTs experience large fluctuations in the generator terminal voltage because of uncontrolled consumption of reactive power. During grid fault conditions, the FSWT consumes large quantities of reactive power to stay grid-connected and prevent the rotor from over-speeding, thereby losing synchronization. It is therefore imperative to provide voltage and reactive power support for the FSWT-power system. This is important to enable the wind power system to fulfill the grid codes as prescribed by the system operator and successfully go through a fault condition. Flexible AC transmission system (FACTS) devices are often used in enhancing the voltage stability and reactive power control in the FSWT- power system. It has been shown however from the available literature that the installation of these devices alongside the WT inflates the total cost of the wind power system thereby making the overall wind system more expensive. The PMSG-WT is becoming more attractive for wind energy systems. This class of WTs has fully-rated converters that control the active and reactive power of the WT, enabling the WT system to ride through a grid fault condition successfully. This improves the low voltage ride through (LVRT) ability during a grid disturbance. This characteristic makes it a very suitable choice for grid-connected operations. A unique feature of this category of wind system is the possibility of controlling its fully rated converters to support a nearby induction generator WT system, making it a suitable choice for the development of a hybrid wind farm. This research proposes exploring this characteristic of the PMSG-WT in developing a hybrid wind system of the PMSG-WT and FSWT. The proposed hybrid wind system utilizes the ability of the PMSG in supporting a nearby wind farm. Therefore, systematic control of the PMSG and FSWTwind system is proposed using the fully rated converters of the PMSG-WT system in providing the required voltage support and reactive power needed by the FSWT-wind system during a grid disturbance. The proposed strategy, therefore, eliminates the need for FACTS devices. To develop the proposed coordinated control strategy of the PMSG and FSWT-hybrid wind power system, a current allocation strategy is first developed for the grid side converter (GSC) of the PMSG. This is based on the converter capacity and current capability of the GSC in providing reactive power needed by the FSWT-based wind system in the event of a grid fault condition. With this approach, the GSC capacity of the PMSG is utilized efficiently to improve the LVRT capability of the FSWT-based wind farm and voltage support of the hybrid wind farm. In a steadystate, the control priority ensures that both wind systems operate efficiently and reliably. The proposed solution offers both technical and economic advantages compared to the traditional voltage support methods available to the FSWT-wind system under grid fault conditions. This method can be applied to existing wind power systems operating with the FSWTs and can be further applicable to any new wind farm, which would be established with this hybrid configuration. Results from the proposed strategy show an improvement in the grid voltage of the hybrid wind farm, there is a reduction in grid voltage sags while the FSWT-based wind farm experiences an improvement in its output power and reactive power profile while it rides through a fault condition.